Enhanced Electromechanical Response and Thermal Stability of 0.93(Na1/2Bi1/2)TiO3-0.07BaTiO3 Through Aerosol Deposition of Base Metal Electrodes - Khansur, Neamul Hayet; Eckstein, Udo; Ursic, Hana; Sadl, Matej; Brehl, Martin; Martin, Alexander; Rieß, Kevin; de Ligny, Dominique; Webber, Kyle Grant (Advanced Materials Interfaces, 2021)
Na1/2Bi1/2TiO3-based relaxor ferroelectrics are extensively investigated for use in transduction applications because of their relatively large electromechanical properties. Integration of these materials into devices, however, requires better temperature stability in addition to electromechanical properties. This work demonstrates a novel approach to enhance the temperature stability of the long-range ferroelectric order as well as to enhance electromechanical properties in a non-ergodic relaxor 0.93(Na1/2Bi1/2)TiO3-0.07BaTiO3 (NBT-7BT) without changing the chemical composition through, for example, chemical substitutions or second phase particles. The approach involves the room temperature deposition of copper electrodes directly on the relaxor ceramic substrate using the aerosol deposition (AD) method. The collision of solid-state particles with the substrate surface during AD results in large impact and residual stresses, inherent to the AD process, which are shown with piezo-response force microscopy to induce long-range ferroelectric domain ordering in non-ergodic relaxor NBT-7BT. Using Raman spectroscopy, the magnitude and depth profile of the stress-induced transformation are determined. It is demonstrated that deposition-induced stresses significantly increase the temperature stability of the electromechanical properties, where long-range ferroelectric ordering is observed up to 150 °C, which is approximately 41 °C higher than NBT-7BT samples without the AD processed electrode. Moreover, the AD treatment also facilitates ferroelectric domain switching at a lower electric field, enabling maximum polarization at a relatively lower field and an enhancement in the piezoelectric response. It is shown that the deposition-induced stress is responsible for such an enhancement. Importantly, this impact-stress-driven tailoring of electromechanical properties can potentially be utilized for other functional ceramic materials as well, where internal residual stress can result in enhanced functional properties.
CRIS-Team Scopus Importer:2021-05-21
Keywords: aerosol deposition; deposition-induced stress; electromechanical applications; lead-free relaxors; temperature stability